2020
DOI: 10.48048/wjst.2020.4177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Pathogenic Bacteria in Bulk Tank Raw Milk, Thailand

Abstract: Although there are a number of raw milk collection centers in Nakhon Ratchasima, there is a lack of information with regard to the process of isolation and characterization of foodborne pathogens in raw milk. Therefore, the purpose of this research was to investigate the prevalence and characterization of foodborne pathogens, including Bacillus cereus, Escherichia coli, Listeria monocytogenes, Salmonella spp. and Staphylococcus aureus from 33 raw milk samples from 9 different raw milk collection centers locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…in raw milk was reported in a wide range such as 3-7% in North America, 0-50% in Europe, and about 5% in Iran [9][10][11]. In Tailand, there was not the report of Listeria contamination in raw milk [12]. Unpasteurized or improper processed milk caused three out of 36 outbreaks of listeriosis.…”
Section: Introductionmentioning
confidence: 99%
“…in raw milk was reported in a wide range such as 3-7% in North America, 0-50% in Europe, and about 5% in Iran [9][10][11]. In Tailand, there was not the report of Listeria contamination in raw milk [12]. Unpasteurized or improper processed milk caused three out of 36 outbreaks of listeriosis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, awareness of antimicrobial-resistant Staphylococcus spp. has become the primary concern in public health because it affects not only animals but also milk products routinely consumed by humans [ 9 ]. In the dairy cattle industry, subclinical mastitis is caused by Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In dairy farming in East Java, the lack of production quantity is also offset by the potential for low quality, where the feeding system, milking management, high temperature, and humidity contribute significantly to the contamination of pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli [6,7]. In line with this, Kupradit et al [8] reported that in milking management, the teats of cows or the Milker's hands have a significant effect on bacterial milk contamination. Such contamination can also occur with the movement through the intermediaries of workers, water, and production equipment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It does affect not only human health but also the economic sector [11]. Cases of the food-borne disease have been found due to raw milk consumption [8], contamination with S. aureus, and E. coli bacteria that can come from raw milk. Thus, this study aimed to estimate the prevalence of S. aureus and E. coli from raw milk and the presence of crucial antimicrobial-resistant gene encodings such as the mecA gene in S. aureus and the blaTEM gene in E. coli are expected to provide a clear picture of the findings of the distribution of antimicrobial resistance (AMR) isolated from raw milk in East Java Province, Indonesia.…”
Section: Introductionmentioning
confidence: 99%